Analysis of miRNA Associated with Coronary Artery Calcification. (25th July 2022) - Yang, Ning; Song, Yanqiu; Dong, Bo; Yang, Jingyu; Li, Yang; Qin, Qin; Guo, Zhigang
Abstract : Cardiovascular diseases seriously endanger human physical and mental health and life safety, to investigate correlation between miR-let-7b and miR-29b and coronary artery calcification of various patients. At present, real-time fluorescence quantitative PCR (qRT-PCR) was used to detect the expression levels of plasma miR-let-7b and miR-29b in patients with coronary artery calcification and noncoronary artery calcification and to analyze whether the expression levels of miR-let-7b and miR-29b were different between the two groups. It was shown that there was no significant difference in the expression of miR-let-7d-3p between the two groups. But the expression of miR-29b in the observation group was significantly lower than that in the control group. Taken together, miR-29b might be a risk factor for coronary artery calcification and may be a marker for early diagnosis of coronary artery calcification.